Analisis Risiko Kebencanaan Indonesia untuk Mendukung Kebijakan Publik - Rachman, Muhammad Gazali; Zelvany, Zshelda Tiara; Favali, Falkis Edo; Nugraha, Muhammad Reyfangga Aji Putra (Journal of Infrastructure Policy and Management (JIPM), 2025)
Indonesia is situated within an active tectonic zone, rendering it highly susceptible to earthquakes. Earthquake disasters not only result in physical damages and loss of life but also pose significant challenges in formulating adaptive and risk-based public policies. This study aims to analyze earthquake disaster risk in Indonesia and evaluate the extent to which public policy has addressed this potential hazard. The methodology employed is a literature review using a mixed-methods approach: qualitative analysis to examine geological and social aspects, and quantitative analysis through spatial assessments utilizing Geographic Information Systems (GIS). The analysis is grounded in a conceptual disaster risk framework encompassing three main components: hazard, exposure, and capacity. The findings reveal that the presence of active faults traversing densely populated areas, limited public awareness, and weak enforcement of technical regulations such as the Indonesian National Standard (Standar Nasional Indonesia/SNI) for earthquake-resistant buildings contribute to the high disaster risk. This study recommends the integration of disaster education into the school curriculum, the strengthening of technical regulations such as the earthquake-resistant SNI, and the incorporation of local wisdom in building practices as strategies to enhance community resilience to earthquake disasters.